Study On the Storage Life span of Several Traditional Indonesian Chili : Sambal Terasi, Sambal Pecel, Sambal Rujak - Emma Satriaty Wirakusumah (Media Gizi dan Keluarga, 2001)
The goal of study is to investigate the long-term effect of storing chili in term of storing chili in term of its quality. Emphasis will be specifically focused on three (3) types of chili, Sambal Terasi, Sambal Pecel, and Sambal Rujak. Treatment of product follows a single uniform methodology process; storing in regular room temperature without preservatives, packed in a thin plastic wrap, and sealed in a thick plastic wrap. This study began in April of 1999 and ended in May of 2000. The emphasis of this study concentrates on physical and microbiological analysis. Sambal Kacang can be stored up to five (5) months, where the acceptance capacity by panelists is in the range of 87 ¡V 100 %. Sambal Terasi can only be stored up to 1 (0ne) month. In terms of taste and aroma, Sambal Terasi has an acceptance rate of 50-60% by the second month, but demonstrates an increase of water level and protein, which is expected to increase bacterial growth. Sambal Rujak has the longest storage capacity exceeding eight (8) months. Panelists give an acceptance rate of 83 ¡V 100 %. Sambal Rujak can reach this storage life span due to its high level of sugar. On the other hand, Sambal Kacang spoils faster because of the presence of the rancidity development. In conclusion, the microbiological analysis of Sambal Kacang seems to be complex because its month-to-month development fluctuates, whereas the microbiological analysis of Sambal Terasi and Sambal Rujak supports organoleptic testing results.